RFID Communication Network as a Platform for Student Attendance System - Abu Bakar Nas’sha’aban, Raissuddin Bin (Universiti Teknologi PETRONAS, 2009)
This student attendance system project is based on detection using radio frequency identification (RFID). The attendance system combines both hardware and software to complete. The hardware used are the Activewave’s standard reader and tag. The reader transmits frequency to tag at 433 MHz and receive at 868 MHz. On the other hand, the tag transmits at 868 MHz and receives at 433 MHz. As for the system’s software, it comprises of the Student Attendance List Database, Programming Station and the Student Check-In Program. The first software is open source software, the second is developed by Activewave while the last software is built by the author using Microsoft Visual Basic. The hardware and software are combined and integrated, to produce the attendance system. Troubleshoot and class test are made for the system to determine its functionality and efficiency, and to meet the design objectives.